Hypermetropia as a Risk Factor for Age-Related Macular Degeneration. Review - V. G. Likhvantseva; S. G. Kapkova; A. S. Gevorgyan; E. Yu. Nekrasova (Oftalʹmologiâ)
The authors presented a complete comprehensive analysis of the combined data of 11 cross-sectional (static) and 11 longitudinal cohort studies with follow-up durations of 5 to 14 years, 16 case-control studies, as well as 3 systemic meta-analyses and 1 “umbrella” study evaluating the scientific hypothesis that hypermetropia is a risk factor for the development of age-related macular degeneration (AMD). In these studies, AMD was verified against the diagnostic criteria of three different classification systems: those of the National Eye Institute (USA), the International System for the Study of Age-Related Maculopathy, and the Wisconsin Classification WARMGS. A total of 82308 patients with AMD were enrolled. 3 baseline indicators in the population were analyzed: the initial hypermetropia, the spherical coefficient (SE) and the axial length of the eye (AL), on the one hand, and the prevalence of AMD, on the other hand. Traditional statistical indicators were calculated: the risk ratio (RR) of AMD among hypermetropes compared to emetropes and a 95 % confidence interval (CI). Pooled data from meta-analyses showed significant associations between farsightedness, SE, AL, and the prevalence of early AMD. The combined RR and 95 % CI were: 1.13 (1.06–1.20), 1.10 (1.07–1.14), and 0.79 (0.73–0.85), respectively. An increase in SE by diopter was correlated with early AMD (RR 1.06; 95 % CI 1.02–1.10). The late AMD did not confirm its association with the refractive error. The umbrella meta-analysis lowered the statistical significance of this association for early AMD (RR 1.08, 95 % CI 1.01–1.18); with late AMD (RR 0.84, 95 % CI 0.77–0.91). In general, experts came to the conclusion that the likelihood of developing AMD depends on the refractive status of the patient.